Determining the parameters of maximum runoff of a river basin Elek (Journal of Geography and Environmental Management, 2019)
Determining the parameters of maximum runoff is an important water management task. Characteristicsof the maximum runoff of a spring flooding are widely used in the design and operation of hydraulicengineering constructions. Characteristics of the maximum runoff of the rivers of the basin of the ElekRiver require specification taking into account data of the last 30-40 years. Data on an annual waterrunoff, a layer and the maximum runoff of a spring flooding on the rivers to the basin of the Elek Riverare collected. The settlement period for series of observations (1940-2015) is chosen, series of observationson 13 gauging station with use of the regression analysis are restored, the natural water runoff of theElek and Kargala Rivers taking into account the regulating influences of reservoirs is restored, tables ofthe restored series with the regression equations are made; graph of dependence of the maximum waterdischarge on a runoff layer are received, it is made calculation accuracy assessment of key parametersof a runoff taking into account information volume equivalent to data monitoring, the table of statisticalparameters of the maximal runoff is made and comparison of parameters of a curve of distribution of themaximum runoff of a spring flooding of the rivers of the basin of Elek of two periods of 1940-1974 and1975-2015 are made.